2019
DOI: 10.1016/j.niox.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Variability in nitrate-reducing oral bacteria and nitric oxide metabolites in biological fluids following dietary nitrate administration: An assessment of the critical difference

Abstract: There is conflicting evidence on whether dietary nitrate supplementation can improve exercise performance. This may arise from the complex nature of nitric oxide (NO) metabolism which causes substantial inter-individual variability, within-person biological variation (CV B ), and analytical imprecision (CV A ) in experimental endpoints. However, no study has quantified the CV A and CV B of NO metabolites or the factors that influence their production. These data are important to calculate the critical differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…The ergogenic potential of NO 3 − supplementation is largely dependent on the reduction of concentrated NO 3 − to nitrite (NO 2 − ), which is regulated by anaerobic bacteria in the oral cavity ( 121 123 ). Although the oral microbiome may be disturbed by many oral substances (e.g., antibiotics, antibacterial mouthwash, gum chewing, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ergogenic potential of NO 3 − supplementation is largely dependent on the reduction of concentrated NO 3 − to nitrite (NO 2 − ), which is regulated by anaerobic bacteria in the oral cavity ( 121 123 ). Although the oral microbiome may be disturbed by many oral substances (e.g., antibiotics, antibacterial mouthwash, gum chewing, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…( 124 ), only about 50% of studies reported controlled environments for the oral microbiome; for example, “subjects were asked to abstain from using antibacterial mouthwash and chewing gum…” ( 115 ) Thus, variability in the oral microbiome may contribute to the observed variability in the efficacy of NO 3 − supplementation. Furthermore, recent studies have demonstrated that under controlled conditions, the reduction of NO 3 − to NO 2 − in biological fluids varies substantially within individuals across repeated visits ( 121 ). The large variability in the performance-enhancing effects of NO 3 − supplementation may be due to the profound biological variability of the oral microbiome ( 121 ), and this postulation warrants future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, disruption of oral microbial communities by over-use of antiseptics or antibiotics will interfere with the nitrate–nitrite–nitric oxide pathway ( Kapil et al, 2013 ), as well as food habits with low dietary nitrate ( Ashworth et al, 2015 ). As a result of these, humans appear to vary widely in their NRC ( Doel et al, 2004 ; Liddle et al, 2019 ), with important potential consequences for diseases or conditions that are influenced by a deficit in nitric oxide, ranging from cardiovascular diseases to reduced sport performance or diabetes development, among others ( Lundberg et al, 2018 ). The current work shows that, in oral bacterial communities with a slightly reduced NRC, the supplementation of nitrate may suffice to restore and promote efficient nitrate reduction; however, our data also show that in individuals with extremely low NRC, the addition of a nitrate-reducing probiotic could be instrumental for a recovery of the function.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of nitrate-reducing species varies among individuals and, accordingly, the NRC as well ( Liddle et al, 2019 ). Individuals with low baseline levels of nitrate-reducing species could use nitrate as a prebiotic to increase the levels of these bacteria over time.…”
Section: Introductionmentioning
confidence: 99%